Comparison of immune responses to zirconia, polyether ether ketone (PEEK), and stainless-steel in orthopaedic implants - Agung Riyanto Budi Santoso; Respati Suryanto Dradjat; Edi Mustamsir; Setyawan Purnomo Sakti; Panji Sananta; Hidayat Sujuti; Heri Suroto (Medicinski glasnik, 2026)
Aim: Orthopedic implants must meet specific criteria, including mechanical strength, durability, and biocompatibility. This study compares the immune response of zirconia, polyether ether ketone (PEEK), and stainless-steel implants in vivo, focusing on lymphocyte and fibroblast infiltration as indicators of immune activation. Methods: A total of 27 New Zealand white rabbits were used, with nine animals in each group. Implants of zirconia, PEEK, or stainless steel were surgically placed in the thigh and observed for 4 weeks. Histological analysis measured lymphocyte and fibroblast infiltration at the implant site using a microscope at 400x magnification. Statistical analysis included the Kruskal-Wallis test for group comparisons, followed by Mann-Whitney and Bonferroni correction for pairwise comparisons. Results: The Kruskal-Wallis test showed significant differences in lymphocyte (p=0.002) and fibroblast (p=0.003) counts among the groups. Zirconia exhibited significantly lower lymphocyte (median=0.5) and fibroblast (median=1.0) infiltration compared to stainless steel (lymphocytes: median=3.0, fibroblasts: median=2.0), and PEEK (lymphocytes: median=2.0, fibroblasts: median=3.0). Bonferroni correction confirmed zirconia showed the least immune activation (p<0.0167). Conclusion: Zirconia offers superior biocompatibility with minimal immune response, making it an ideal material for orthopedic implants, particularly for patients with metal sensitivities. PEEK showed moderate immune activation but is helpful for non-load-bearing applications. Stainless Steel induced the highest immune response due to the release of metal ions and corrosion. Zirconia is the most biocompatible material tested, making it a promising choice for orthopedic implants.
Keywords: immunity; polyetheretherketone; prostheses and implants; stainless-steel; zirconia.